Insight into Cd Detoxification and Accumulation in Wheat by Foliar Application of Ferulic Acid - Simeng Li; Wenyang Fu; Bingling Li; Yi Wang; Yiran Cheng; Houyang Kang; Jian Zeng (Plants)
Cadmium (Cd) contamination in agricultural soils poses a significant threat to human health through the food chain. It is of great significance to address safe wheat production in Cd-contaminated agricultural soils. This study employed foliar spraying of ferulic acid (FA) in both hydroponic and field trials to investigate its potential in alleviating Cd toxicity and reducing Cd accumulation in wheat grains. Our findings revealed that FA application at 20 and 50 μM promoted plant growth, increased photosynthetic efficiency, and enhanced root tolerance to Cd by increasing mean root diameter, surface area, and root tip number, as well as enhancing antioxidant defense in roots. Especially, 20 μM FA foliar application significantly alleviated Cd-induced growth inhibition in seedlings and reduced grain Cd content by 66.3% compared to Cd-stressed alone. Mechanistically, FA downregulated the Cd transporter gene TaHAM2 to reduce Cd translocation from roots to shoots, while upregulated the Cd cellular compartment gene TaHAM3 to increase root Cd retention, of which 82.9% was sequestered in roots. During the grain-filling period in the field trial, FA application reduced Cd transport from roots to stems and stems to rachides, but enhanced Cd retention in rachides and roots. Additionally, FA downregulated the phloem Cd loading gene LCT1, limiting Cd allocation to bracts and grains, which in turn lowered the Cd content in the grains. Collectively, FA foliar application modulated Cd transport pathways by coordinately downregulating xylem and phloem transporter genes and enhancing root Cd retention capacity. These findings established FA as a promising strategy for Cd detoxification and reduced accumulation in crop grains through integrated physiological and molecular interventions. Overall, it holds potential for the future development of safe crop production in soils polluted with Cd.